Implicature of Smart Tourism in Enhancing the Reputation of Tourism Destinations - Muharis, Muharis; Taufik, Muhammad; Citra Kencana, Nimas (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
Tourism is a significant economic factor at the global level, making direct contributions to GDP, employment, and cultural exchange. The development of smart tourism, where information and communication technology (ICT) is integrated with mainstream tourism activities, has transformed the competitive landscape of destinations, enhanced the visitor experience, and fostered a positive reputation. While smart tourism presents opportunities, it also poses threats, primarily in terms of infrastructural preparedness, digital divides, and low community awareness of utilizing technology to drive tourism development. The research will explore the implications of adopting smart tourism on enhancing the reputation of destinations and elaborate on the primary challenges of merging digital innovations with traditional practices. A qualitative descriptive approach was employed through a systematic review and analysis of the literature, including academic journals, books, reports, and relevant online sources. The findings are that smart tourism can play a greater role in enhancing destination image through easier access, convenience, and personalization by ICT, geographic information systems (GIS), and big data. The technologies also promote sustainability by tracking the environmental impacts and enhancing visitors' awareness of local cultural protection and nature conservation. Infrastructure and human capacity limitations, as well as digital divides, remain the most significant obstacles that hinder the efficacy of smart tourism efforts. Multi-stakeholder collaboration, involving local society, the private sector, and the state, is emphasized in the research to facilitate the effective integration of technology in tourism. Smart tourism is therefore ultimately both a tool of global competitiveness strategy and a path toward sustainable, technology-based destination management.